LEGAL ANALYSIS OF DEFAULT IN SALE AND PURCHASE TRANSACTIONS USING THE CASH ON DELIVERY PAYMENT METHOD ON THE SHOPEE MARKETPLACE - Mufijar Ajam (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2026)
The development of the e-commerce banking system in Indonesia has led to the rise of the Cash on Delivery (COD) payment method, which is a popular choice among consumers. However, the practice of COD also poses a risk of default: consumers refusing to pay or accept goods without a valid reason, which is detrimental to sellers and couriers. This study aims to analyse the problem of default in COD transactions on the Shopee marketplace from the perspectives of positive law, muamalah fiqh, and the Consumer Protection Law. The research method employs a normative-empirical approach, including a review of legal documents and the literature, as well as interviews with Shopee consumers and couriers. The results of the study show that COD transactions have the characteristics of a cash sale-and-purchase agreement (bai’mutlaq) but contain elements of uncertainty (gharar) for the seller. Formal law enforcement is limited to small transactions, so platform law becomes a practical mechanism for resolving disputes internally. This study emphasises the need to strengthen regulations, transparent internal marketplace procedures, and consumer legal education to ensure that COD transactions are fair, safe, and in accordance with Sharia principles.